Pengaruh Kepuasan Kerja, Dan Komitmen Organisasional Terhadap Kinerja Karyawan Yang Dimoderasi Oleh Motivasi Kerja Di Yayasan Wakaf Darussalam Subah - Inka Nuromavita (Jurnal Ekonomika dan Bisnis, 2023)
In the current era of globalization, the challenges of rapid environmental change and the advancement of information technology that the organization's sensitivity in response to changes that occur in order to remain exist and productive. The reason of the problem in this research is "How to influence job satisfaction, and organizational commitment, to employee performance moderated by work motivation variable at Teachers Yayasan Wakaf Darussalam ". The purpose of this study was to analyze the effect of job satisfaction, and organizational commitment, on employee performance moderated by work motivation variable at Teachers Yayasan Wakaf Darussalam. sampling for respondents in this study is to use the census method, where each member of the population as a whole is used as a sample. The number of samples in this study as many as 105 respondents who became the sample in this study are all Teachers of Yayasan Wakaf Darussalam consisting of three Schools namely: MTS Darussalam, MA Darussalam, and SMK Darussalam.The result of the research shows that job satisfaction variable has positive and significant effect on employee performance, organizational commitment has positive and significant effect to employee performance, work motivation variable strengthens the relationship between job satisfaction to employee performance, and motivation variable strengthens the relationship between organizational commitment variable to employee performance Nissan Service Center Semarang City. Keywords: Job Satisfaction, Organizational Commitment, Work Motivation and Employee Performance.